The Perception of Educators on Gender Equality: A Study in Ecuador - Diaz, Veronica; Vallejos, Henry; Oval Soto, Carmen Paz; Carrasco, Selin; Coloma, Carmen; Flores, Fabiola; Lozada, Carola; Rivera, Patricio; Simon, Maria (My University, 2024)
Gender equality is a prerequisite for people-centered human development. This exploratory and descriptive study was conducted to investigate the perception of gender among Ecuadorian primary school teachers. Quantitative data were obtained from teachers in public and urban educational establishments. In order to collect the data, an online survey-type opinion questionnaire was applied with the aim of finding out teachers' perception of gender equality within their institutions in educational establishments in the Republic of Ecuador, considering the dimensions of personal perceptions of the subject, the organizational culture, and the implementation of gender equality in the internal management of the educational organizations where they work. The results of the questionnaire show that teachers perceive that there is currently more receptiveness to gender issues than in the past. From the answers received, it can be concluded that people identify with gender issues, even though there is a need for elements and support to enable them to be expressed effectively, on a daily basis and sustained over time.
Keywords: gender equality; sustainable development goals; teachers; urban schools; basic education; ecuador